Long-term Adhesion Study of Self-etching Systems to Plasma-treated Dentin - Hirata, Ronaldo; Teixeira, Hellen; Almeida Ayres, Ana Paula; Machado, Lucas S. [UNESP]; Coelho, Paulo G.; Thompson, Van P.; Giannini, Marcelo (Quintessence Publishing Co Inc, 2015)
Purpose: To determine the influence of atmospheric pressure plasma (APP) treatment on the microtensile dentin bond strength of two self-etching adhesive systems after one year of water storage as well as observe the contact angle changes of dentin treated with plasma and the micromorphology of resin/dentin interfaces using SEM. Materials and Methods: For contact angle measurements, 6 human molars were sectioned to remove the occlusal enamel surface, embedded in PMMA resin, and ground to expose a flat dentin surface. Teeth were divided into two groups: 1) argon APP treatment for 30 s, and 2) blown air (control). For the microtensile test, 28 human third molars were used and prepared similarly to contact angle measurements. Teeth were randomly divided into 4 groups (n = 7) according to two self-etching adhesives and APP treatment (with/without). After making the composite resin buildup, teeth were sectioned perpendicular to the bonded interface to obtain beam specimens. The specimens were tested after 24 h and one year of water storage until failure. Bond strength data were analyzed by three-way ANOVA and Tukey's post-hoc test (a = 0.05%). Three beam specimens per group that were not used in the bond strength test were prepared for interfacial SEM analysis. Results: APP application decreased the contact angle, but increased the bond strength only for one adhesive tested. SEM evaluation found signs of degradation within interfacial structures following 1-year aging in water. APP increased the dentin surface energy, but the effects of APP and 1-year water storage on dentin bond strength were product dependent. Conclusion: APP increased the dentin surface energy. It also increased the bond strength for Scotchbond Universal, but storage for one year negated the positive effect of APP treatment.
Keywords: plasma; microtensile; dentin adhesion